Pengaruh Pengangguran, Produktivitas, Kemiskinan, Pertumbuhan Ekonomi Terhadap Ketimpangan Pendapatan Di Jawa Timur - Shobary, robert; Bambang Eko Afiatno (Jurnal Ekonomika : INDEPENDEN, 2025)
Income inequality is a crucial issue in economic development in Indonesia, given its significant impact on social and economic stability. This study analyzes the effects of unemployment, labor productivity, poverty, and economic growth on income inequality in regencies/cities in East Java Province from 2018 to 2024, using the Generalized Method of Moments (GMM). The analysis results show that unemployment and poverty variables do not have a statistically significant effect on income inequality. Conversely, labor productivity was found to have a negative and significant effect, indicating that increased productivity tends to reduce income inequality. Meanwhile, economic growth has a positive and significant effect, indicating that economic growth actually increases income inequality. Based on these findings, it can be concluded that increasing labor productivity is a key factor in efforts to reduce income inequality. Furthermore, the results regarding the positive effect of economic growth indicate problems in the distribution of the benefits of economic growth, where economic growth is not enjoyed equally by all levels of society.